Construction of Structures with Thin-Section Ceramic Masonry - Cinta Lluis-Teruel; Josep Lluis i Ginovart (Buildings)
Current regulatory principles focus on resistance and durability to ensure long-term robustness while optimizing sections to maximize efficiency and minimize material use, thus enhancing sustainability and reducing environmental impact. Historical ceramic masonry constructions fully adhere to these principles; however, they have been largely supplanted by modern materials. The compressive strength and functional advantages of structures built with ceramic masonry, particularly those featuring extremely thin wall sections, warrant a reassessment of their structural properties. This is exemplified by thin-tile vaults (ranging from 0.015 to 0.020 m in thickness) and hollow brick vaults with a thickness of less than 0.050 m, both of which represent highly efficient solutions. The proposed examples inherently meet these structural system properties due to their low energy dispersion, minimal gravitational weight, superior thermal performance, and monolithic tectonic composition using a single, easily recyclable material. This paper reviews the historical background of these construction systems, emphasizing their relevance in post-war periods when concrete and steel were scarce. It is concluded that these construction systems remain valid and are consistent with the principles of the circular economy, as well as with the structural safety standards of the 21st century.